Ultrasonic impact grinding machine tool and process development - Reilly, Michael (University of Dublin, Trinity College, 2013)
Ultrasonic Impact Grinding (UIG) is a mechanical material removal process used to erode holes and cavities in hard and brittle materials such as glass, ceramics, silicon carbide, quartz and titanium as examples by using shaped tools, high frequency mechanical motion and an abrasive slurry. An old but relatively unknown technique in the micromechanical systems community, the process is effective whether the workpiece material is conducting or not. The machined workpiece has little or no subsurface damage and does not suffer thermal damage. The process has numerous advantages such as the ability to machine high tolerance through holes, to carry out micromachining, and to carry out cutting at high aspect ratios. Ultrasonic impact grinding is often preferred over conventional machining approaches as it can machine intricate features in advanced materials with hardness values of greater than 40 Rockwell Hardness (HRC). The use of CNC control to generate motion profiles for ultrasonic impact grinding is emerging as a new area of interest. The objective of the work presented in this thesis was to design, develop and commission a bench-top computer numerically controlled (CNC) ultrasonic impact machine tool.The development of the ultrasonic impact grinding machine tool was based on the adaption of a traditional 3 axes machining platform and the integration of a CNC control system. An ultrasonic system to include an ultrasonic generator and ultrasonic stack – converter, booster and sonotrode were integrated into the machine tool. An abrasive slurry delivery system and workpiece clamping system was also designed and developed in the project work. The developed ultrasonic impact grinding machine tool has been shown to successfully machine brittle materials and detailed process characterisation investigations were undertaken. A number of process measurement systems have been integrated into the ultrasonic impact grinding machine tool and the process has been characterised and a process parameter window for successful machining operations have been identified. In-process measurements of process forces were undertaken and demonstrated significant insight into the ultrasonic impact grinding process, as well as insight into pre and post engagement conditions. Investigations based around the machine feed levels, amplitudes of displacement of the vibrating tool, process force levels and machining distances has allowed detailed process analysis to be carried out. A machine vision based wear measurement system was integrated in order to have in-situ measurement of tool wear .It has been shown that a CNC ultrasonic impact grinding machine with the associated in- process force and toll wear vi measurement systems provides significant insight into the ultrasonic impact grinding process. The platform developed within the research will provide a platform for future research in ultrasonic impact grinding.
PUBLISHED